Influence of Ce Doping on the Electrical and Optical Properties of TiO2 and Its Photocatalytic Activity for the Degradation of Remazol Brilliant Blue R. (4th November 2013) - Malik, Aisha; Hameed, S.; Siddiqui, M. J.; Haque, M. M.; Muneer, M.
Abstract : Nanocrystalline TiO2 particles doped with different concentrations of Cerium (Ce, 1–10%) have been synthesized using sol-gel method. The prepared particles were characterized by standard analytical techniques such as X-ray diffraction (XRD), FTIR and Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM). The XRD analysis shows no change in crystal structure of TiO2 after doping with different concentrations of Ce, which indicates the single-phase polycrystalline material. The SEM analysis shows the partial crystalline nature of undoped, and doped TiO2 and TEM analysis shows the particle sizes were in the range of 9–14 nm in size. The a.c. analysis shows that the dielectric constant ε and dielectric loss tan δ decrease with the increase in frequency. The dielectric property decreases with the increase in dopant concentration. It is also observed that the impedance increases with an increase in dopant concentration. The photocatalytic activity of the synthesized particles (Ce-doped TiO2 ) with dopant concentration of 9% (Ce) showed the highest photocatalytic activity for the degradation of the dye derivative Remazol Brilliant Blue R in an immersion well photochemical reactor with 500 W halogen linear lamp in the presence of atmospheric oxygen.